Steroid Cell Ovarian Neoplasm, Not Otherwise Specified: A Case Report and Review of the Literature - Paul Singh; Frank Deleon; Ralph Anderson (Case Reports in Obstetrics and Gynecology)
Background. Steroid cell ovarian tumors, not otherwise specified, represent a unique cause of female virilization. Most commonly encountered in premenopausal women, these tumors can exist throughout a women’s lifetime, from before puberty until after menopause. Case. Steroid cell, not otherwise specified, was diagnosed in a 70-year-old female significant for hirsutism. The patient demonstrated elevated total testosterone levels with normal gonadotropins, DHEA, and DHEA-S levels. CT imaging revealed a right ovarian mass and subsequent laparoscopic right oophorectomy yielded clinical improvement promptly. Conclusion. Virilization in females can occur based on ovarian or adrenal pathology. In terms of ovarian-based female virilization, many tumors exist that may induce women to demonstrate masculine features, such as pure Sertoli, pure Leydig, Sertoli-Leydig combinations, and gynandroblastomas. Each of these tumor types possesses a unique histologic pattern that allows for pathologic identification after removal. A rare source of ovarian-based female virilization is steroid cell neoplasms, not otherwise specified, that do not demonstrate these specific histologic characteristics and thus represent a diagnosis of exclusion after other causes of ovarian-based female virilization have been ruled out.